Significance of Initial Chest CT Severity Score (CTSS) and Patient Characteristics in Predicting Outcomes in Hospitalized COVID-19 Patients: A Single Center Study - Aleksandra Milenkovic; Simon Nikolic; Zlatan Elek; Jelena Aritonovic Pribakovic; Aleksandra Ilic; Kristina Bulatovic; Milos Gasic; Bojan Jaksic; Milan Stojanovic; Dusica Miljkovic Jaksic; Arijeta Kostic; Roksanda Krivcevic Nikolcevic; et al. (Viruses)
The aim of this study is to examine the prognostic role of initial chest computed tomography severity score index (CTSS) and its association with demographic, socio-epidemiological, and clinical parameters in COVID-19 hospitalized patients. A retrospective study included patients who were hospitalized in the COVID Hospital of the Clinical Hospital Center Kosovska Mitrovica from July 2020 to March 2022. We compared patient characteristics and outcome of their hospital stay with values of CT severity score (mild, moderate, and severe form of the disease). Patients with severe disease were statistically significantly older, they treated more days, and they presented statistically significant highest mortality rate compared to mild and moderate forms. Smokers and obese were significantly more frequent among patients with higher CT, while vaccinated patients were more common among those with a mild form. Biochemical parameters at admission also showed statistical significance between the examined groups. We can conclude that by employing the initial CT severity score as the strongest predictor of mortality, it is possible to predict the outcome in hospitalized patients. A comprehensive examination of the patient upon admission, including determining the extent of inflammatory changes in the lungs using computed tomography, the levels of oxygen saturation, and other laboratory parameters, can assist doctors in making an adequate clinical evaluation and apply appropriate therapeutic protocols in the treatment of COVID-19.